Necesidad de Reformar la Ley de Sanidad Vegetal en su Art. 35, en lo referente a las sanciones administrativas, mismas que violentan el debido proceso al limitar el derecho a la defensa - Briceño Castillo, Marlo Bolívar (2016)
This academic work, complies with the provisions issued by the National University of Loja, in relation to the legal research that is necessary in a thesis. Which it starts at the beginning with the literature review, in which important aspects of the investigation will find, as is a legal review of the law on plant health. The constitution of Ecuador regarding the vegetable law and the complementary rules thereof. I started to continue the doctrinal framework, it discusses the following points: Legal Aspects of infringements in the Ecuadorian legal norms; and Judgment of administrative and environmental law violations in the plant health and related standards. Already in the legal framework, we talk of the right to due process and fundamental part of the prosecution of contraventions. It also continues with details of the materials and methods used in research. The procedures and techniques, and the results of field research. To end with verification of objectives corresponding weighted conciliation proposal for legal reform.